Pemantauan Tingkat Bisphenol A (BPA) dalam Air Sumur sebagai Indikator Pencemaran Lingkungan - Kusuma Sari, Mustika; Yogana, Ridwan Andri (Universitas Sarjanawiyata Tamansiswa, 2024)
Urban areas often face greater environmental pollution challenges compared to rural areas, primarily due to high population density, industrial activities, and inadequate waste management systems (Huang et al., 2012). Well water, frequently used as a drinking water source in many urban areas, is susceptible to contamination by various pollutants, including Bisphenol A (BPA) This study aims to monitor BPA levels in well water in urban areas as an indicator of environmental pollution Well water samples from several strategic locations were analyzed using UV-Vis spectroscopy, an effective technique for detecting and measuring BPA levels in water The results showed variations in BPA concentrations by location. For instance, in Pakem, BPA concentrations ranged from 0.68 to 1.91 mg/L, in Ngemplak from 0.27 to 3.55 mg/L, and in Ngaglik from 1.37 to 1.91 mg/L. No direct pattern was found linking BPA concentration to population density. This variation is likely due to environmental factors, industrial activities, or consumption habits of the urban population. Although some locations have BPA concentrations below the EPA's safe contamination limit, this study highlights the importance of monitoring and managing health risks associated with BPA pollution in urban areas.